Pengaruh Brand Image dan Promosi Tiktok Terhadap Keputusan Pembelian Di Poljam Mart - yuni ariska; Dedi Handoko; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2026)
This study aims to determine the effect of Brand Image and TikTok Promotion on Purchase Decisions of consumers at Poljam Mart. This research employs a quantitative method with data collected through questionnaires distributed to 91 respondents. Prior to data analysis, the research instruments were tested using validity and reliability tests. The results indicate that all questionnaire items have r-count values greater than r-table values, and the Cronbach’s Alpha value is 0.70, indicating that the instruments are valid and reliable. Data analysis was conducted using multiple linear regression, including t-test, F-test, and coefficient of determination (R²). The results show that partially, Brand Image has a significant effect on Purchase Decisions with a significance value of 0.000 < 0.05, while TikTok Promotion also has a significant effect on Purchase Decisions with a significance value of 0.028 < 0.05. Simultaneously, Brand Image and TikTok Promotion have a significant effect on Purchase Decisions, as indicated by an F-value of 67.539 and a significance value of 0.000. The coefficient of determination (R²) of 0.606 indicates that 60.6% of purchase decisions are influenced by Brand Image and TikTok Promotion, while the remaining 39.4% are influenced by other factors outside this study. Keywords: Brand Image, TikTok Promotion, Purchase Decision.